Students’ Perceptions on Educational Environment of Selected Dental Colleges in Bangladesh (Bangladesh Journal of Medical Education, 2020)
This descriptive type of cross-sectional study was conducted with the aim to find out the students’ perceptions on educational environment of selected dental colleges in Bangladesh. The study was carried out in ten selected dental colleges (4 government & 6 non-government) of Bangladesh. Total sample size was 1169 of different years of BDS students. Dental colleges were selected purposively & data was collected from students by adopting convenience sampling technique. Data collection was done with self-administered semi-structured questionnaire with two open questions using Dundee Ready Educational Environment Measurement (DREEM) inventory with some modification. There were five subscales of DREEM for students. Study results revealed that total DREEM score of students were 142. Mean score of students’ perceptions by subscale of DREEM were “students’ perception of their learning (34.95); students’ perception of their teachers (30.36); students’ academic self-perception (24.94); students’ perception of educational atmosphere (32.82) and students’ social self-perception (18.83). All these values indicated that the students’ perception were in the right & mostly positive direction. Study recommended that significant attention should be paid in few problematic areas specially for “too much teacher centered learning and over emphasized factual learning. Study also recommended to improve the logistic support for students of dental colleges to ensure better educational environment of Bangladesh.Bangladesh Journal of Medical Education Vol.11(2) 2020: 27-33